2011
DOI: 10.5732/cjc.011.10188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bevacizumab plus chemotherapy in Chinese patients with metastatic colorectal cancer: a randomized phase III ARTIST trial

Abstract: The efficacy and safety of bevacizumab with modified irinotecan, leucovorin bolus, and 5-fluorouracil intravenous infusion (mIFL) in the first-line treatment of metastatic colorectal cancer (mCRC) has not been well evaluated in randomized clinical trials in Chinese patients. We conducted a phrase III trial in which patients with previously untreated mCRC were randomized 2:1 to the mIFL [irinotecan (125 mg/m2), leucovorin (20 mg/m2) bolus, and 5-fluorouracil intravenous infusion (500 mg/m2) weekly for four week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 13 publications
4
82
1
Order By: Relevance
“…Individual patient data were pooled from seven RCTs of bevacizumab in the first-line (AVF2107, NO16966, ARTIST, AVF0780, AVF2192, AGITG MAX) and second-line (E3200) treatment of mCRC (Table 1) [1][2][3][4][5][6]16]. Previously published phase II and III studies were selected based on (1) their design as RCTs evaluating chemotherapy with or without bevacizumab for mCRC; (2) the use of identical definitions and procedures for collecting patient baseline characteristics, along with primary and secondary efficacy endpoints and safety assessments; and (3) the ability to access individual patient information within study databases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual patient data were pooled from seven RCTs of bevacizumab in the first-line (AVF2107, NO16966, ARTIST, AVF0780, AVF2192, AGITG MAX) and second-line (E3200) treatment of mCRC (Table 1) [1][2][3][4][5][6]16]. Previously published phase II and III studies were selected based on (1) their design as RCTs evaluating chemotherapy with or without bevacizumab for mCRC; (2) the use of identical definitions and procedures for collecting patient baseline characteristics, along with primary and secondary efficacy endpoints and safety assessments; and (3) the ability to access individual patient information within study databases.…”
Section: Methodsmentioning
confidence: 99%
“…The data from this trial, AVF2107, showed that bevacizumab prolonged both overall survival (OS) and progression-free survival (PFS) when added to irinotecan, bolus fluorouracil, and leucovorin. Subsequently, data from additional randomized controlled trials (RCTs) have demonstrated the efficacy and safety profiles of bevacizumab among a wider variety of patients with mCRC, in combination with multiple backbone chemotherapy regimens, and in different treatment settings [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the subsequent NO16966 study of bevacizumab in combination with Oxa-CT (XELOX or FOLFOX4) for first-line treatment of mCRC patients (Saltz et al, 2008), the MAX study of bevacizumab in combination with capecitabine monotherapy or capecitabine and mitomycin for first-line treatment of mCRC patients, and the AVEX study of bevacizumab in combination with single-agent capecitabine therapy for first-line treatment of elderly mCRC patients (Cunningham et al, 2013), positive primary endpoint results were obtained. Similarly, the phase Ⅲ, randomized ARTIST study of first-line treatment of Chinese patients with mCRC confirmed that bevacizumab in combination with a modified IFL regimen significantly improved efficacy in comparison with the modified IFL regimen alone (Guan et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…35 As aforementioned, the additional benefits of BEV were not consistent across trials. As for OS, no efficacy of additional BEV to CTX could be identified in several trials, including FLU + LEU, 22,23 IFL, 10 FOLFOX4, 30 and CAP 29,30 based chemotherapy regimens. However, after being stratified based on the CTX, the addition of BEV to FLU + LEU and FOLFOX based chemotherapy showed evident efficacy; its additional benefit was also evident in IFL-based chemotherapy after ignoring the trial 10 leading greatly heterogeneity, suggesting that prior surgery treatment for CRC maybe a main confounding factor; as for CAP-based chemotherapy regimens, both trials 29,30 identified no additional benefits of BEV.…”
Section: Discussionmentioning
confidence: 99%